PENGARUH KOMITE AUDIT DAN KUALITAS AUDIT TERHADAP TAX AVOIDANCE DI PERUSAHAAN MANUFAKTUR FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Dwi Fitrianingsih; Putri Wulandari (LP2M Universitas Bina Bangsa, 2024)
This study was conducted to determine the Effect of the Audit Committee and Audit Quality on Tax Avoidance in Food and Beverages Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 Period. The number of samples taken was 13 Food and Beverages Manufacturing Companies that were included in the criteria. The audit committee is measured by the number of audit committee members and the quality of the audit is measured by dummy variables. Tax avoidance as a dependent variable is measured by the cash effective tax rate (CETR). The method used to analyze the relationship between variables in this study is multiple linear regression analysis. The results of the Hypothesis test show that the Audit Committee has a significant positive effect on Tax Avoidance, Audit Quality has a negative insignificant effect on Tax Avoidance. Simultaneously, the Audit Committee and Audit Quality Have a Significant Positive Effect on Tax Avoidance